Investigation of Properties of Polymer/Textile Fiber Composites - KOÇAK, EMİNE DİLARA; USTA, İSMAİL; TAŞDEMİR, MÜNİR (TAYLOR & FRANCIS AS, 2010)
Polymer-based composite structures have advantages over other materials. The most important advantage is the higher mechanical properties obtained from the composites when supported by fiber reinforcement. The mechanical and thermal properties of fiber-reinforced composite structures are affected by the amount of fibers in the structures, orientation of the fiber and fiber length. Silk and cotton fibers are used in many fields but especially in clothing and textiles. However, there is not enough research on their usage as reinforcement fibers in composite structures. Silk fibers as a textile material have better physical and mechanic properties than other animal fibers. It is very important that the improvement of the mechanical and physical properties of the composite structures allows them to be used in many areas. From economical, technological and environmental points of view, the improved the mechanical and physical properties of polymeric materials are receiving much attention in the recent studies. In this study, various lengths (1mm-2.5mm and 5mm) of waste silk and waste cotton fibers were added to high-density polyethylene (HDPE) and polypropylene (PP) polymer in the mixing ratios of (polymer:fiber) 100%:0%, 97%:3%, and 94%:6% to produce composite structures. On the other hand, known lengths (1-2.5-5mm) of waste silk and waste cotton fibers were added to recycled polyamide-6 (PA6) and polycarbonate (PC) polymers in mixing quantities of 100%-0%, 97%-3%. A twin-screw extruder was employed for the production of composites. Tensile strength, % elongation, yield strength, elasticity modulus, Izod impact strength, melt flow index (MFI), heat deflection temperature (HDT), and Vicat softening temperature properties were determined. In order to determine the materials' thermal transition and microstructure properties, differential scanning calorimetry (DSC) and scanning electron microscopy (SEM) were used. Results have shown that cotton and silk fibers behave differently than in the composite structure. Waste silk fiber composites give better mechanical properties than waste cotton fiber.
Keywords: cotton; polyamide; polycarbonate; polyethylene; polymer composites; polypropylene; silk; NATURAL FIBERS; BIOCOMPOSITES; JUTE